L'approche culturelle en géographie : une autre appréhension de l'espace - Paul Claval (Confins)
Present from the birth of human geography, the cultural approach throve mainly after the cultural turn of the discipline. Made of whatever is not innate in human beings, culture is the DNA of human societies. Passing down from generation to generation, it includes representational and non-representational components. It is not the societies of orality, the written word and medias. It structures social space in networks and around forums. It involves intelligence, emotivity and imagination and doubles the world with imaginaries spaces serving as counterpoints to reality and instituting a normative order. The space it explores is not only that of vital necessities: it is also that of leisure and pleasure as well as that of wars and catastrophes; that of human bodies, and of the environment.The cultural approach revolutionizes the study of places in analyzing their varied forms of hierarchization and the role played today by their visibility. It substitutes a territorial approach qui stress the human investment in places to the older regional analysis. It focuses on identities and the processes of imitation and distinction they are linked to and to their spatial expression. The cultural approach is responsible for a global restructuration of human geography and its economic components. It adds to the socio-political and socio-economic analyses which constituted its social component a socio-cultural analysis that is responsible for the contemporary expansion of cultural geography.